2016
DOI: 10.1128/aem.00493-16
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Toluene Degraders in the Rhizosphere of a Constructed Wetland Model Show Diurnal Polyhydroxyalkanoate Metabolism

Abstract: Constructed wetlands (CWs) are successfully applied for the treatment of waters contaminated with aromatic compounds. In these systems, plants provide oxygen and root exudates to the rhizosphere and thereby stimulate microbial degradation processes. Root exudation of oxygen and organic compounds depends on photosynthetic activity and thus may show day-night fluctuations. While diurnal changes in CW effluent composition have been observed, information on respective fluctuations of bacterial activity are scarce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
(66 reference statements)
3
17
0
Order By: Relevance
“…Within this PFR, a circulating flow regime prevents the formation of large chemical gradients and an efficient turnover of organic carbon occurs [13]. In previous studies on a PFR running for several years with toluene as sole external carbon source, it was shown that toluene was mainly degraded aerobically by members of the Burkholderiales [14, 15]. However, several cultivation-independent analyses suggested that microbes able to degrade toluene anaerobically were also plentiful.…”
Section: Introductionmentioning
confidence: 99%
“…Within this PFR, a circulating flow regime prevents the formation of large chemical gradients and an efficient turnover of organic carbon occurs [13]. In previous studies on a PFR running for several years with toluene as sole external carbon source, it was shown that toluene was mainly degraded aerobically by members of the Burkholderiales [14, 15]. However, several cultivation-independent analyses suggested that microbes able to degrade toluene anaerobically were also plentiful.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important observation is the overall increase in TW studies directly investigating microbial communities over the last four years. Given this exceptional trend and overall research activity, the author suggests that the field of TWs is working to move beyond the black-box understanding which has been referenced as recently as 2016 (see Lünsmann et al [32]). Following this first known activity assessment, the first study utilizing enumeration was found in 1994, the first study utilizing a structural analysis was found in 2001, and the first microbial community function study in 2004.…”
Section: Presentmentioning
confidence: 99%
“…Perhaps the most important observation is the overall increase in TW studies directly investigating microbial communities over the last four years. Given this exceptional trend and overall research activity, the author suggests that the field of TWs is working to move beyond the black-box understanding which has been referenced as recently as 2016 (see Lünsmann et al [32]). …”
Section: Presentmentioning
confidence: 99%
See 2 more Smart Citations